Spatial incoherence-driven optical reconstruction of holograms with observer shift-invariance - Yeo Ju Sohn; Daeho Yang (Light: Science & Applications)
Abstract Coherence preserves phase consistency between wavefields, enabling accurate recording and reconstruction in holography. Although recent advances in computational optics have realized holographic data acquisition using incoherent light by computationally retrieving information, optical reconstruction still requires partially coherent light sources. We demonstrate a hologram that reconstructs 3-dimensional distribution utilizing incoherence. By decomposing incoherent light into infinitesimal coherent lights and calculating their propagations, the incoherent sum is optimized to resemble the desired 3-dimensional scene, whereas individual coherent lights reconstruct completely different intensities. Incoherence provides high image quality and a wide eyebox, with the reconstructed intensity remaining shift-invariant under pupil displacement, allowing a 1000-fold expansion of the eyebox. We confirm the shift-invariance through a proof-of-concept experiment and demonstrate real-time synthesis of incoherent holograms using a neural network, significantly reducing computational costs. Our method could inspire new approaches in photonics using incoherent light and be practically adopted in holographic displays.